New species of Xestochironomus Sublette et Wirth, 1972 (Diptera: Chironomidae) from Atlantic Forest, Brazil - Pinho, Luiz Carlos; Souza, João Francisco (Zootaxa, 2013)
Two new Xestochironomus species, X. dickinsoni sp. n. and X. virgoferreae sp. n., from Brazilian Atlantic Forest are de-scribed, based on male adults. Additionally, a key to adult males of the genus is provided.